Effects of Actinobacillus pleuropneumoniae cytotoxins on generation of oxygen radicals by porcine neutrophils - Tarigan, Simson (Indonesian Journal of Animal and Veterinary Sciences, 1999)
Cytotoxins produced by Actinobacillus pleuropneumoniae (App) suggested to be the most important pathogenic and virulent factors for this organism. However, the mechanisms on how the cytotoxins contribute to the disease process remain unclear. The purpose of this study is to investigate the effect of the cytotoxins on the oxidative-burst metabolism of porcine neutrophils. In this study, neutrophils were firstly loaded with an oxidative probe dichlorofluorescin diacetate (DCFHDA) then expose to cytotoxins. Cells producing oxygen radicals emitted fluorescence and its intensity was measured with a FACScan flow cytometer. All cytotoxins derived from either App serotypes producing ApxI and ApxII, App serotypes producing ApxII only, or App serotypes producing ApxII and ApxIII were capable of stimulating neutrophils for oxygen-radical generation. However, compared with phorbol myristate acetate (PMA), App cytotoxins were much weaker as stimulants for oxygen radicals. In addition, Apx preparation stimulated an oxidative-burst metabolism of neutrophils at a low, narrow range of Apx doses. At higher doses, the toxins inhibit the oxidative burst metabolism. The effects of cytotoxins produced by App during infection on recruited neutrophils into the lungs are assumed to be comparable to those observed in this in vitro study. Neutrophils, and other host cells, adjacent to the bacteria become lysis due to high toxin concentration, whereas those at some distance to the bacteria produce oxygen radicals which in turn cause tissue damage or necrosis. Â  Key words: Actinobacillus pleuropneumoniae, cytotoxin, Apx, neutrophils, pig, oxygen radical, flow cytometry Â